PERUBAHAN TERITORI RUANG PADA RUMAH SUBSIDI TIPE 30 (Studi Kasus : Perumahan Mawar Indah, Kendal) - Pratama, Bagus Iqbal Adining; Wijayanti, Wijayanti; Sari, Suzanna Ratih (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2021)
Abstract: The supply of subsidized housing in Indonesia is rising rapidly. One of them is Mawar Indah residence, Kaliwungu, Central Java. The current problem with subsidized houses is in the house planning that does not consider the needs and developments of the occupants of the house. It causes subsidized housing to have low standard quality, as a result, the occupants make spatial development that will involve changes in spatial territory. The purpose of this research is to ascertain changes in space territory and its effects on occupant privacy and comfort. This research applies a qualitative approach and descriptive methods. A purposefully select sampling technique was used to determine 3 samples of houses that had experienced space development. The study results show changes in space territory, making the privacy and comfort of residents not fulfilled. The changing spatial territory is more dominant in the area of semi-public space and private space, this is because residents develop space to accommodate the needs of family social and economic activities. In this case, the living room and family are used for economic activities as a shop. This causes a lack of privacy and comfort for occupants.Abstrak: Penyediaan rumah subsidi di Indonesia saat ini berkembang dengan cepat. Salah satunya adalah di perumahan Mawar Indah, Kaliwungu, Jawa Tengah. Permasalahan yang terjadi saat ini pada rumah subsidi yaitu perencanaan rumah yang tidak melihat kebutuhan dan perkembangan dari penghuni rumah tersebut. Hal ini menyebabkan rumah subsidi memiliki kualitas di bawah standar, akibatnya warga di perumahan tersebut melakukan pengembangan ruang yang akan memengaruhi perubahan teritori ruang. Tujuan dari peneltian ini ialah untuk mengetahui perubahan teritori ruang dan pengaruhnya terhadap privasi dan kenyamanan penghuni. Penelitian ini menggunakan pendekatan kualitatif dan metode deskriptif. Teknik sampling purposefully select digunakan untuk menentukan 3 sampel rumah yang telah mengalami pengembangan ruang. Hasil studi menunjukkan perubahan teritori ruang, membuat privasi dan kenyamanan penghuni tidak terpenuhi. Teritori ruang yang berubah lebih dominan pada area ruang semi publik dan ruang privat, hal tersebut karena, warga melakukan pengembangan ruang dalam upaya untuk mengakomodasi kebutuhan aktivitas sosial dan ekonomi keluarga. Dalam hal ini, ruang tamu dan keluarga digunakan untuk aktivitas ekonomi sebagai toko. Hal tersebut menyebabkan kurangnya privasi dan kenyamanan penghuni.